NOTES ON THE ARITHMETIC-GEOMETRIC MEAN INEQUALITY FOR SINGULAR VALUES - Ruan, Jiechang (Italian Journal of Pure and Applied Mathematics, 2015)
In this short note, we present a generalization and a new equivalent form of the arithmetic-geometric mean inequality for singular values. Meanwhile, we also show some remarks related to generalizations of the arithmetic-geometric mean inequality for singular values.